The impacts of geometry and binding on CaMKII diffusion and retention in dendritic spines - Byrne, Michael J. (2010)
We used a particle-based Monte Carlo simulation to dissect the regulatory mechanism of molecular translocation of CaMKII, a key regulator of neuronal synaptic function. Geometry was based upon measurements from EM reconstructions of dendrites in CA1 hippocampal pyramidal neurons. Three types of simulations were performed to investigate the effects of geometry and other mechanisms that control CaMKII translocation in and out of dendritic spines. First, the diffusional escape rate of CaMKII from model spines of varied morphologies was examined. Second, a postsynaptic density (PSD) was added to study the impact of binding sites on this escape rate. Third, translocation of CaMKII from dendrites and trapping in spines was investigated using a simulated dendrite. Based on diffusion alone, a spine of average dimensions had the ability to retain CaMKII for duration of ~4 s. However, binding sites mimicking those in the PSD controlled the residence time of CaMKII in a highly nonlinear manner. In addition, we observed that F-actin at the spine head/neck junction had a significant impact on CaMKII trapping in dendritic spines. We discuss these results in the context of possible mechanisms that may explain the experimental results that have shown extended accumulation of CaMKII in dendritic spines during synaptic plasticity and LTP induction.